2019
DOI: 10.3389/fnhum.2019.00058
|View full text |Cite
|
Sign up to set email alerts
|

Pre-attentive Mismatch Response and Involuntary Attention Switching to a Deviance in an Earlier-Than-Usual Auditory Stimulus: An ERP Study

Abstract: An acoustic stimulus elicits an electroencephalographic response called auditory event-related potential (ERP). When some members of a stream of standard auditory stimuli are replaced randomly by a deviant stimulus and this stream is presented to a subject who ignores the stimuli, two different ERPs to deviant and standard stimuli are recorded. If the ERP to standard stimuli is subtracted from the ERP to deviant stimuli, the difference potential (DP) waveform typically exhibits a series of negative-positive-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…At the scalp level and in intracortical electrodes, slow electrical oscillations do seem to anticipatorily track the structure of periodic auditory stimuli [87,88], and this tracking is associated with the subjective passage of time [89]; these oscillations could be explored as possible estimates of mean underlying phase, with particular focus on those in motor areas. Ideally, timing prediction errors could be observed in the evoked EEG response to events (the ERP), allowing a direct measurement of event expectancy at each event time, and there are indeed indicators that the ERP is sensitive to temporal predictability (e.g., [90,91]); however, the sensitivity of the ERP to recent stimulus history makes this approach unpromising. However, timing prediction errors may be observable in EEG/MEG through their effect on gamma oscillations [92,93].…”
Section: Pippet In the Brainmentioning
confidence: 99%
“…At the scalp level and in intracortical electrodes, slow electrical oscillations do seem to anticipatorily track the structure of periodic auditory stimuli [87,88], and this tracking is associated with the subjective passage of time [89]; these oscillations could be explored as possible estimates of mean underlying phase, with particular focus on those in motor areas. Ideally, timing prediction errors could be observed in the evoked EEG response to events (the ERP), allowing a direct measurement of event expectancy at each event time, and there are indeed indicators that the ERP is sensitive to temporal predictability (e.g., [90,91]); however, the sensitivity of the ERP to recent stimulus history makes this approach unpromising. However, timing prediction errors may be observable in EEG/MEG through their effect on gamma oscillations [92,93].…”
Section: Pippet In the Brainmentioning
confidence: 99%
“…In addition to MMN and P300, a further late ERP component is referred to index prediction errors in the brain. This component, known as the reorienting negativity or RON, appears as a negative deflection at 400-600ms in response to reorientation of attention to the predictive/standard stimuli after it has been switched (indexed by P300) towards the preceding deviant stimuli (Correa-Jaraba et al, 2016; Ungan et al, 2019). Even though our study could not cover this ERP since it did not come out as a prominent peak in the subtraction waveforms ( Figure 1 ), especially in the audio only modality, we argue that RON too would, being a late component, have common brain generators like P300 across modalities and it is also shown to be centred upon fronto-central regions in extant literature (Correa-Jaraba et al, 2016; Justo-Guillén et al, 2019; Ungan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the processing of prediction error becomes amodal at the P300 level itself and is not something that is attained at further later stages during the reorienting negativity (RON). The RON in the brain appears as a negative deflection at 400-600ms in response to the reorientation of attention to the predictive/standard stimuli after it has been switched (indexed by P300) towards the preceding deviant stimuli (Correa-Jaraba et al, 2016; Ungan et al, 2019). Even though in our analysis we could not cover this ERP since it did not come out as a prominent peak in the subtraction waveforms ( Figure 1 ), we argue that RON too would, being an even later component, have common brain generators across modalities, probably more frontal, as also reported in recent studies (Correa-Jaraba et al, 2016; Justo-Guillén et al, 2019; Ungan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At the scalp level and in intracortical electrodes, slow electrical oscillations do seem to anticipatorily track the structure of periodic auditory stimuli [85, 86], and this tracking is associated with the subjective passage of time [87]; these oscillations could be explored as possible estimates of mean underlying phase, with particular focus on those in motor areas. Ideally, timing prediction errors could be observed in the evoked EEG response to events (the ERP), allowing a direct measurement of event expectancy at each event time, and there are indeed indicators that the ERP is sensitive to temporal predictability (e.g., [88, 89]); however, the sensitivity of the ERP to recent stimulus history makes this approach unpromising. However, timing prediction errors may be observable in EEG/MEG through their effect on gamma oscillations [90, 91].…”
Section: Discussionmentioning
confidence: 99%